Obtención de una resina alquídica a partir de aceite de palma crudo a escala laboratorio (2010)
The article presents the preparation of an alkyd resin using phthalic anhydride, glycerin and crude palm oil proceeding of a sample from Cumaral, Meta- Colombia. The process of the resin’s formulation was performed in function of the oil length. The operational conditions were determined for the reactions of alcoholysis and esterification. The resin was also carried out in a reaction system, which consists of a stirred-stainless reactor with heat system and control, afterwards, some operational conditions were changed and the results evaluated. The resin obtained in the reactor was used in the preparation of enamel.